Body Mass Index and Associated Factors of School Absenteeism by School Feeding Program at Selected Primary Schools in Addis Ababa, Ethiopia: A Comparative Study - Solomon Muluken Ayehu; Addisu Tadesse Sahile (Scientifica)
Background. Quality of education plays a crucial role in the social, economic, and political development of a nation. Primary school is a vital stage in developing the personality and consciousness of school children. Objective. The study assessed the Body Mass Index and factors associated with School Absenteeism at selected primary schools in Addis Ababa, 2018. Methods. A comparative cross-sectional study was undertaken on 324 (162 each group) from selected primary schools of Addis Ababa from May 02 to July 30, 2018. All participants and their families provided written informed consent and assent. A systematic random sampling technique was used to select participants, where the list of students was once identified from the selected schools. An independent t-test was undertaken at p value <0.05 as the statistically significant level. And, binary logistics regression was used for the identification of factors statistically associated with school absenteeism, with its respective 95% confidence interval (CI) and p value of <0.05 significant level. Findings. There was a statistically significant difference between feeding and nonfeeding participants on average weight, school absenteeism, and BMI for age, at p<0.05. Participants who enrolled in the school feeding program had a higher average weight than nonfeeding participants (p<0.05). Participants from the feeding group had lower average school absenteeism than their counter participants (p<0.05). The average BMI for age was significantly higher among feeding participants than nonfeeding participants (p<0.05). The odds of having school absenteeism were 1.796 times higher among feeding participants than among nonfeeding participants (AOR: 1.796; 95CI:1.061–3.042, p<0.05). The odds of sustaining absenteeism from the school were 2.257 times higher among feeding participants than among nonfeeding participants (AOR: 2.257; 95%CI: 1.291–3.948; p<0.05). Conclusion. A higher number of school absenteeism, average weight, and BMI for age were observed in participants enrolled in the school feeding program than those who did not get enrolled in the feeding program. Large-scale studies were recommended to testify the impacts of school feeding on absenteeism.